72 The butterfly project – improving treatment escalation planning in the emergency department. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Keillor, Lisa; Edwards, Sarah; Gildoni, Sofia; Jackson, Dianne; Murray, Karen; Platts, Margaret; Salim, Jamila; Satchell, Freya; Simpson-Millard, Jeanette; Russ, Kate
Abstract : Background: The 2017 End of Life Care Hospital Improvement Programme (ELCHIP) audit of deaths at the Leicester Royal Infirmary (LRI) an Emergency Department (ED) attendance may be an opportunity to proactively identify and plan for deterioration. The clinical frailty scale (CFS) can identify older people at increased risk of deterioration or dying and local data suggests a 1 year mortality rate of 50% in the cohort of patients with CFS 7–9. Methods: The Butterfly Project is a multidisciplinary quality improvement project aiming to increase the percentage of older people CFS 7–9 dying in their preferred place of care, with additional outcomes based on early identification of uncertain recovery and treatment escalation planning. ED notes were reviewed for all CFS 7–9 patients dying within 30 days of an ED attendance between February 2019 and May 2020. Interventions were broadly within two streams. The first focused on improving treatment escalation planning including verbal and visual prompts and the introduction of the ReSPECT process. The second was based on improving the skillset of ED staff via educational interventions. Results: Between May 2019 and May 2020, although there was no change in the percentage of patients dying in their preferred place of care, statistical process control charts showed sustained upward shift in: Identification and communication of uncertain recovery Documented CPR decision Clear, individualised treatment escalation plan ReSPECT introduction had the most significant impact on treatment escalation planning, although incremental improvements were seen with verbal nudges to action at staff handover. Conclusions: Sustained verbal and visual prompts, in conjunction with introduction of the ReSPECT process and educational support, can increase early identification and communication of uncertain recovery and prompt treatment escalation. Ensuring that these improvements translate into patients dying in their preferred place of care is complex and requires organisational collaboration.